Total Solar Irradiance Variation During Rapid Sunspot Growth - Zahid, H. Jabran (2004)
Large sunspot areas correspond to dips in the total solar irradiance (TSI), a phenomenon associated with the local suppression of convective energy transport in the spot region. This results in a strong correlation between sunspot area and TSI. During the growth phase of a sunspot other physics may affect this correlation; if the physical growth of the sunspot resulted in surface flows affecting the temperature, for example, we might expect to see an anomalous variation in TSI. In this paper we study NOAA active region 8179, in which large sunspots suddenly appeared near disk center, at a time (March 1998) when few competing sunspots or plage regions were present on the visible hemisphere. We find that the area/TSI correlation does not significantly differ from the expected pattern of correlation, a result consistent with a large thermal conductivity in solar convection zone. In addition we have searched for a smaller-scale effect by analyzing white-light images from MDI (the Michelson Doppler Imager) on SOHO. A representative upper-limit energy consistent with the images is on the order of 3×1031 ergs, assuming the time scale of the actual spot area growth. This is of the same order of magnitude as the buoyant energy of the spot emergence even if it is shallow. We suggest that detailed image analyses of sunspot growth may therefore show `transient bright rings' at a detectable level.